Hepatitis C treatment and injecting drug users in Perth, Western Australia: Knowledge of personal status and eligibility criteria for treatment - Carruthers, Susan; Ryan, C. (2012)
Background: Few injecting drug users (IDU) in Australia take part in antiviral therapy for chronic hepatitis C (HCV). To assess whether IDU are aware of the eligibility criteria for treatment and their personal HCV status, we surveyed 78 IDU attending the fixed-site needle exchange in the city of Perth. Method: Participants were eligible for the study if they self-reported having ever been diagnosed as HCV antibody positive. Each participant completed a semi-structured questionnaire administered by a peer HCV educator at the needle exchange. Results: Knowledge of personal HCV status was poor with more than half of the group not knowing the purpose of a polymerase chain reaction test. Knowledge of treatment eligibility was also poor especially around issues relating to alcohol consumption, the need for a liver biopsy, and treatment during pregnancy. Conclusion: Up-to-date information about eligibility criteria for HCV treatment has not filtered down to this group of older IDU. Furthermore, knowledge of personal HCV status (chronic infection and infectivity) needs to be improved. Informed decisions about treatment cannot be made if knowledge of status is poor and IDU are not familiar with treatment eligibility. © 2012 Informa UK Ltd.